2015
DOI: 10.1111/voxs.12180
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the blood component production process

Abstract: Background Automation of blood component preparation (BCP) from whole blood (WB) collections can help to optimize the BCP process, and it is increasingly being widespread implemented.Aim This review summarizes the quality of blood components obtained with new automated devices developed in the 2000s.Methods We reviewed available literature on the quality of blood components obtained with new automated devices.Results Blood components obtained with the new devices met European standards. Of note, compared with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Other beneficial aspects of automating blood processing systems include improved standardization of outputs, increased productivity, operator satisfaction and system usability, reduced wastage and reductions in required space and operator skill requirements, as well as reduced potential for repetitive strain injury to operators [3,5,6,9,32]. In addition, reduction in the required space and the number of operators also decreases the movement of operators around the workspace, which could play a major role in preventing the spread of diseases such as COVID-19.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other beneficial aspects of automating blood processing systems include improved standardization of outputs, increased productivity, operator satisfaction and system usability, reduced wastage and reductions in required space and operator skill requirements, as well as reduced potential for repetitive strain injury to operators [3,5,6,9,32]. In addition, reduction in the required space and the number of operators also decreases the movement of operators around the workspace, which could play a major role in preventing the spread of diseases such as COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors have also reported that full automation may contribute to a balance between standardization and customization. Also, the released resources would enable the effortless implementation of other technologies in the blood component laboratory [3,5,32]. In addition, standardization of semi-automated processing methods remains highly variable among centres, with the remaining manual steps continuing to impact wastage as well as the quality and safety of blood products [3,5].…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study analysing the impact on corrected 1‐h corrected count increment (CCI) and the transfusion interval did not find significant differences with the manual method . Subsequently, new generation of automation devices have been introduced in the marked which are reviewed elsewhere .…”
Section: Automation In Platelet Preparationmentioning
confidence: 99%